Agama, Segregasi Ekonomi, dan Pemberdayaan Masyarakat Jayapura Papua - Idrus al Hamid (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
Regional expansion in Papua is an interesting phenomenon, because there is an attraction between the central government and the Papuan. The pretext of the development and empowerment of Papua, both from the aspect of natural resources and human resources is the reason that made the Presidential Instruction in 2003 published for the acceleration of development in Papua. The pros and cons occured, because the Papuans do not want the expansion at that time, until four victims have to fall. Inequality occured because natural resources in Papua are explored more by non-Papuans. Friction between OAP (Papuan Genuine) and ONP (Non-Papuan) has occurred since the 1960s to the present. But later OAP began to understand the pattern of changing times and preparedness in the face of the globalization era, especially the readiness to face an increasingly developing economy. The friction that occured due to different culture and history in the economic dynamics between OAP and ONP becomes a meeting point, so that between OAP and ONP now can be established mutual symbiosis, both have their own bargaining value